2022
DOI: 10.3839/jabc.2022.011
|View full text |Cite
|
Sign up to set email alerts
|

Eriodictyol induces apoptosis via regulating phosphorylation of JNK, ERK, and FAK/AKT in pancreatic cancer cells

Abstract: Although it has been intensively studied over the past few decades, pancreatic cancer remains one of the most lethal cancers. Eriodictyol, a plant-derived flavonoid mainly found in citrus fruits, exerts diverse biological effects, including antioxidant, anti-cancer, and anti-inflammatory properties. In this study, we investigated the anticancer properties of eriodictyol and its mechanisms of action in pancreatic cancer cells. In both SNU213 and Panc-1 cells, eriodictyol decreased viability, induced apoptosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Toxicodendron vernicifluum (TV) or Rhus verniciflua Stokes is another traditional herbal medicine native to China, India, Japan, and Korea and is a source of flavonoids and polyphenols such as eriodictyol (ERI), fisetin (FIS) and QUE [ 37 ]. ERI and FIS share a similar backbone structure to those of API, KMF, and QUE ( Figure 1 d) and have also shown some anticancer potential in several cancer models such as breast, colon, and pancreas cancers [ 38 , 39 , 40 , 41 , 42 ]. In 2020, Li et al showed that the extract of TV (TVE) inhibited the interaction of PD-1/PD-L1 in a dose-dependent manner (IC 50 ~26 µM in a competitive ELISA— Table 1 ).…”
Section: Moleculesmentioning
confidence: 99%
“…Toxicodendron vernicifluum (TV) or Rhus verniciflua Stokes is another traditional herbal medicine native to China, India, Japan, and Korea and is a source of flavonoids and polyphenols such as eriodictyol (ERI), fisetin (FIS) and QUE [ 37 ]. ERI and FIS share a similar backbone structure to those of API, KMF, and QUE ( Figure 1 d) and have also shown some anticancer potential in several cancer models such as breast, colon, and pancreas cancers [ 38 , 39 , 40 , 41 , 42 ]. In 2020, Li et al showed that the extract of TV (TVE) inhibited the interaction of PD-1/PD-L1 in a dose-dependent manner (IC 50 ~26 µM in a competitive ELISA— Table 1 ).…”
Section: Moleculesmentioning
confidence: 99%
“…ERK is affected by various epigenetic modifications, including DNA methylation and histone modifications [13,14], and these modifications can affect its expression. For example, phosphorylation of Erkl/2 has a protective effect on the survival of rat axons and neurons [15,16], and conversely, phosphorylation of ERK and FAK/AKT can induce apoptosis [17]. Thus, epigenetic modifications of ERK can have both pro-and anti-apoptotic effects depending on the specific situation [18].…”
Section: Introductionmentioning
confidence: 99%